Relationship between Rafflesia host (Tetrastigma sp.) with plant community and microhabitat characteristics in Jerantut Tambahan Forest Reserve, Mukim Ulu Cheka, Jerantut District, Pahang (Hubung kait perumah Rafflesia (Tetrastigma sp.) dengan komuniti tumbuhan dan ciri mikrohabitat di Hutan Simpan Jerantut Tambahan, Mukim Ulu Cheka, Daerah Jerantut, Pahang) - Abd Razak, Siti Nurfaeiza; Khamis, Shamsul; Juhari, Mohd Afiq Aizat (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study assessed the plant species composition and community structure of the habitats of Rafflesia populations and its relationship with microhabitat at the Jerantut Tambahan Forest Reserve, Ulu Cheka, Jerantut, Pahang. The plant community survey utilised nested circle plot sampling with 10 m radius which include trees with 1.0 cm diameter at breast height (DBH) and above. A total of 62 species from 45 genera, 25 families, and 99 individuals were recorded. Dipterocarpaceae recorded the highest family with six species, followed by Fabaceae and Euphorbiaceae both with five species. The total tree density was 396 individuals/ha (ind/ha) with Fabaceae recorded the highest with 44 ind/ha. The total basal area was 18.55 m2/ha where Dipterocarpaceae contributed the highest with 9.20 m2/ha at the family level, while at the species level, Shorea ovalis was the highest with 8.30 m2/ha and had the highest importance value index at 16.45%. The value of Shannon Diversity Index (H’) was 3.86, Evenness Index of 0.94 and Margalef Richness Index (15.5). This study recorded that soil pH influences the occurrence of four out of eight Rafflesia populations. This finding aid in conservation efforts by highlighting the key environmental factors that need to be maintained or restored to support Rafflesia habitats. Besides, the results are useful in predicting other potential sites where Rafflesia might thrive based on similar environmental conditions.